hdFg haldiya leIlaulafehn
Answers
Answered by
2
Step-by-step explanation:
Let 45=a2−b2 , then 45=(a+b)(a−b) . Also, a+b and a−b have the same parity. So we need to find two odd or two even factors of 45 .
We have that 45=45×1=15×3=9×5 .
For 45×1 , we have a+b=45,a−b=1 . Adding both expressions we get 2a=46 , a=23 , and b=22 . Effectively 45=529−484 .
For 15×3 we have a=9 , and b=6 , for 45=81−36.
Finally for 9×5 we get a=7 , b=2 , for 45=49−4
Answered by
0
Answer:
Please ask questions here and your text is not clear..
Similar questions
English,
3 months ago
Math,
3 months ago
Accountancy,
6 months ago
Math,
1 year ago
History,
1 year ago